Study of Fluid Dynamics In Waterfall Damarwulan Jember As Material For Designing Student Work Sheet - Didit Prasetyo; Bambang Supriadi; Rayendra Wahyu Bachtiar (Pancaran Pendidikan, 2017)
This study aims to review the dynamics of the fluid in the flow Damarwulan waterfall as material to design student worksheets in physics high school. This type of research is descriptive. The results showed that the water flow speed in the cross sectional area of 7,167 cm2 and 2,876.2 cm2 was 4.7 cm/s and 14.1 cm/s. Measurements on another stream with a cross sectional area of 4,752 cm2 and 1,697.5 cm2 current rate is 9.4 cm/s and 28.2 cm/s. While the water flow speed in the waterfall show at a height of 5.49 m and 3.01 m is 10.37 m/s and 7.68 m/s. The density rate waterfall A and B of 1.05 m3/s and 0.78 m3/s so potential micro hydro generated is 56,866.765 W and 23,117.44 W. The results of research conducted that data in accordance with the theory, so can be used as the material for designing student worksheets for learning physics in high school.